Komunikasi Interpersonal Mahasiswa Baru Ditinjau Dari Tawadhu' Dan Penyesuaian Diri - Putri Nabila Bilicha; Putri Nilam Bachry; Ratna Azkia Rakhmandari; Ahmad Rusdi (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study aimed to determine the relationship between tawadhu'and self adjustment to interpersonal communication among the students of University X in Yogyakarta. Respondents in this study are 166 students at University X of Yogyakarta. Analisys data used assumption test, hypothesis test and different test. Interpersonal communication was measured using the scale of Yulianto (2010) based on the theory of De Vito (1997), tawadhu 'was measured using the scale of Thalib's (1991) theory and self-adjustment was measured using the scale used by Wahyudi (2012) based on Fatimah (2010). The results of the study have shown that there is a significant positive relationship between tawadhu'and interpersonal communication on the new students at University X of Yogyakarta, and there is a positive relationship between self-adjustment and interpersonal communication to new students at Universitas X of Yogyakarta.